1996
DOI: 10.1021/bi960984y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Flanking Sequences on the Dimer Stability of Human Immunodeficiency Virus Type 1 Protease

Abstract: The maturation of the human immunodeficiency virus type 1 protease (PR) from the Gag-Pol polyprotein is dependent on the intrinsic proteolytic activity of the dimeric Gag-Pol. Herein, we report the kinetics and conformational stabilities of two unique fusion proteins of the protease. In one, X28-PR, a random sequences of 28 amino acids (X28) was linked to the N terminus of the mature protease. In the second construct, X28-delta TF*PR*delta Pol, X28 is fused to the protease which is flanked at both its termini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 16 publications
6
61
1
Order By: Relevance
“…15 N and 1 H chem- ical shifts of the terminal residues, e.g. Ile 3 and Ala 95 , of PR T26A /DMP323 are nearly identical to those of the PR/ DMP323, implying very similar terminal ␤-sheet arrangements of PR and PR T26A .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…15 N and 1 H chem- ical shifts of the terminal residues, e.g. Ile 3 and Ala 95 , of PR T26A /DMP323 are nearly identical to those of the PR/ DMP323, implying very similar terminal ␤-sheet arrangements of PR and PR T26A .…”
Section: Resultsmentioning
confidence: 89%
“…3D), which makes it ideal for studies of the mature PR dimer either free or bound to a native substrate (22). The mutation D25N may also influence the dimer stability of the mature protease (K D ϭ ϳ10 Ϫ6 M), 3 albeit to a much lesser extent than the mutants that form monomers discussed above (also see Table I). The construct PR D25N/Q2C/L97C was used to optimize the protocol for disulfide bond formation (see "Experimental Procedures" for details).…”
Section: Disulfide Bridge Formation Between the N-and C-terminal Stramentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments indicate initial cleavage by a precursor protease still embedded in the GagPol chain occurs through an intramolecular, concentration-independent mechanism with the precursor protease cleaving its own terminus (4) and critically modulated by the N-terminal region (5)(6)(7)(8). Mutations that block N-terminal cleavage result in severe loss of efficiency in catalytic activity.…”
mentioning
confidence: 99%
“…1) by kinetics and NMR revealed that the very low catalytic activity of the protease precursor prior to the cleavage at the N terminus is due to a much higher dimer dissociation constant (K d ) as compared with the mature protease (11). Upon intramolecular cleavage at the N terminus, the protease forms a stable dimer and exhibits a very low K d (Ͻ10 ϫ 10 Ϫ9 M in 50 mM sodium acetate, pH 5, at 25°C (8,13)). This suggests that inhibition of the protease function either by preventing or by disrupting dimer formation prior to its maturation provides an attractive avenue for inhibitor design.…”
mentioning
confidence: 99%